2007
DOI: 10.1097/gim.0b013e31812e6220
|View full text |Cite
|
Sign up to set email alerts
|

Randomized comparison of phone versus in-person BRCA1/2 predisposition genetic test result disclosure counseling

Abstract: Purpose: This study evaluated whether phone results were equivalent to in-person result disclosure for individuals undergoing BRCA1/2 predisposition genetic testing. Methods: A total of 111 of 136 subjects undergoing education and counseling for BRCA1/2 predisposition genetic testing agreed to randomization to phone or in-person result disclosure. Content and format for both sessions were standardized. Data from the State-Trait Anxiety Inventory and the Psychological General Well-Being index were collected at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
88
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(96 citation statements)
references
References 34 publications
5
88
3
Order By: Relevance
“…While studies suggest that results from a cancer susceptibility tests have the same impact on patients whether they are delivered in person or over the telephone, this is, to our knowledge, the first study to date that has addressed the preference of communication methods that are not in-person. 18,19 In addition, related to the sensitive nature of specific types of tests is the impact of patients' trust in the confidentiality of the information. Studies reporting a preference for US mail or telephone call reflect patients' perceptions that these are the most secure forms of communication.…”
Section: Discussionmentioning
confidence: 99%
“…While studies suggest that results from a cancer susceptibility tests have the same impact on patients whether they are delivered in person or over the telephone, this is, to our knowledge, the first study to date that has addressed the preference of communication methods that are not in-person. 18,19 In addition, related to the sensitive nature of specific types of tests is the impact of patients' trust in the confidentiality of the information. Studies reporting a preference for US mail or telephone call reflect patients' perceptions that these are the most secure forms of communication.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has shown that telephone reporting of genetic test results does not compromise patient knowledge or psychological outcomes, costs less than in-person reporting, and is preferred by some patients. 8 In our clinic setting, the decision to report most cancer genetic test results over the phone rather than in person was made about a year before the current study. This change has resulted in shortened waiting time for new clinic visits and has been essentially neutral from a reimbursement viewpoint, because the time slots previously reserved for these face-to-face follow-up visits have been devoted to other types of patients.…”
Section: Discussionmentioning
confidence: 99%
“…The potential for using telemedicine in clinical genetics service delivery has been highlighted by a number of authors, [19][20][21] who have suggested that it may enable more equitable access to genetics services for people who must otherwise travel long distances to specialist centers. Indeed, an increasing number of studies are exploring alternative models of service provision, including genetic counseling over the telephone, 22,23 and genetics consultations via real-time videoconferencing, 24 so as to improve equality of access, improve cost efficiency, and help to meet the increasing demand for these services.…”
mentioning
confidence: 99%